Life Experiences of Drought Affected Families: Need of Intervention: Understanding the Impact of Drought on Health and the Need for Tailored Interventions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Drought is one of the natural disasters in many parts of the world and a normal, recurrent feature of climate. Drought sets off a vicious cycle of socio- economic impacts beginning with crop-yield failure, unemployment, erosion of assets, decrease in income, worsening of living conditions, poor nutrition and subsequently decreased risk of absorptive capacity, thus increasing vulnerability of the poor to another drought and other shocks. The main focus of the study is to know the life experiences of drought affected families with special reference health. Study revealed that drought has significant impact on economic status, psychological (distress) and physical health of the respondents which need well tailored interventions.